2022
DOI: 10.3390/toxins14020135
|View full text |Cite
|
Sign up to set email alerts
|

Functional EL-HN Fragment as a Potent Candidate Vaccine for the Prevention of Botulinum Neurotoxin Serotype E

Abstract: Clostridium botulinum produces botulinum neurotoxin (BoNT), which is the most toxic known protein and the causative agent of human botulism. BoNTs have similar structures and functions, comprising three functional domains: catalytic domain (L), translocation domain (HN), and receptor-binding domain (Hc). In the present study, BoNT/E was selected as a model toxin to further explore the immunological significance of each domain. The EL-HN fragment (L and HN domains of BoNT/E) retained the enzymatic activity with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…In recent years, the L and/or HN domains of BoNTs have been proved to generate protective antibodies [ 35 , 36 , 42 , 43 ]. In our studies, we also found that the L-HN molecules of BoNT serotypes A, B, and E have strong immunoprotective effects [ 30 , 37 , 38 ] as per the reports of Shone et al on the translocation and effector domains BoNT/A and B [ 44 ]. The L-HN molecule of BoNT/E has been shown to have better immunoprotective efficacy than its Hc domain [ 32 ], which indicated that the L-HN molecule is superior to toxoid vaccines in terms of production and immune protection efficacy.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In recent years, the L and/or HN domains of BoNTs have been proved to generate protective antibodies [ 35 , 36 , 42 , 43 ]. In our studies, we also found that the L-HN molecules of BoNT serotypes A, B, and E have strong immunoprotective effects [ 30 , 37 , 38 ] as per the reports of Shone et al on the translocation and effector domains BoNT/A and B [ 44 ]. The L-HN molecule of BoNT/E has been shown to have better immunoprotective efficacy than its Hc domain [ 32 ], which indicated that the L-HN molecule is superior to toxoid vaccines in terms of production and immune protection efficacy.…”
Section: Discussionsupporting
confidence: 87%
“…To further study the biological properties and functions of FL-HN at the cellular level, neuro-2a cells were selected as the cell model for related experiments. The molecules derived from BoNT/F were incubated with neuro-2a cells, and the activity of FL-HN was assessed by Western blotting, which could detect the content of cleaved rVAMP2 protein at the cellular level [ 36 , 37 , 38 , 39 ]. After co-incubating FL-HN with neuro-2a cells for 12 h, proteins in the cells were extracted for Western blotting detection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations